Hypocupremia-related anemia and neutropenia late after Roux-en-Y gastric bypass surgery (Annals of Medical Research, 2024)
Roux-en Y gastric bypass (RYGB) is a type of surgery that is both restrictive in food intake and malabsorptive. The prevalence of copper deficiency (hypocupremia) has been reported as 10%-%20 after RYGB. Copper deficiency has started to appear more frequently due to bariatric surgical procedures, which are widely applied all over the world and in our country, but it is often not recognized. In order to raise awareness on the subject, we wanted to present a patient who developed copper deficiency and secondary anemia and neutropenia after RYGB.
Keywords: RYGB; Hypocupremia; Anemia